Maps Between Fréchet Algebras Which Strongly Preserve Distance One - Zivari-Kazempour, Abbas (Eurasian Mathematical Journal, 2023)
The paper proves that if \( T : X → Y \) is a 2-isometry between real linear 2-normed spaces, then \( T \) is affine whenever \( Y \) is strictly convex. It also shows that every surjective mapping \( T : A → B \) between real Fréchet algebras, which strongly preserves distance one, is affine under certain conditions.